Distribution regularity of downwash airflow under rotors of agricultural UAV for plant protection - Liu, Xin; Zhang, Wei; Fu, Haiba; Fu, Xiaoming; Qi, Liqiang (International Journal of Agricultural and Biological Engineering, 2021)
In the plant protection spray operation of UAVs, the process of droplet from formation to sedimentation target is affected by airflow, easy to form uneven deposition. Accurately description of rotor downwash flow field, clarification of velocity vector distribution at different heights of the UAV rotor flow field, simulation of the flow field with high precision, which are the prerequisites for accurately analyzing the droplet deposition distribution in rotor downwash flow field. Based on CFD method, the detail of rotor flow field was numerically calculated. Taking LTH-100 single-rotor agricultural UAV as the research object, the three-dimensional solid model of UAV was established, the Reynolds average N-S equation was used as the control equation and the RNG κ-ε as the turbulence model to simulate the flow field of UAV in hover and lateral wind conditions, the wind velocity distribution at different altitudes of rotor downwash flow field was studied. The simulation results of the hover state showed that: In the flow field, the peak velocity appears in a circular distribution below the distal axis of the rotor. With the decrease of height, the peak velocity distribution area showed a tendency to expand gradually after small shrinkage; When the distance from the rotor was not more than 1.5 m, the downwash flow field presented an axisymmetric distribution based on the rotor axis, and the variation rate of velocity in the peak velocity was basically the same, turbulence in downwash flow field made the flow field more complex when the distance from rotor was larger than 2.0 m. On this basis, the optimal flight altitude of UAV is 1.5 m. Wind velocity test of the flow field was carried out on a rotor test bench, wind velocities at four altitudes of 0.5 m, 1.0 m, 1.5 m and 2.0 m were measured to verify the coincidence between the simulated and measured values. The test results showed that: the relative error between the measured and simulated values at four measurement heights were between 0.382-0.524, and the overall average relative errors was 0.430, which verified the confidence level of simulated values for measured values. When the lateral wind velocity was 3 m/s, 4 m/s and 5 m/s, the simulation results showed that: The distribution trend of airflow velocity at the same altitude in lateral-wind flow field with different wind speeds was similar; When the lateral wind speed was 5 m/s, the coupling field formed by the lateral wind and rotor airflow cannot reach the height of 2 m below the rotor. The results of this study can provide more accurate environmental conditions for theoretical analysis of droplet deposition regularity in the flow field, and also provide methodological guidance for the related research on rotor flow field of multi-rotor UAV. Keywords: aviation plant protection, downwash flow field, distribution regularity, numerical simulation, single-rotor UAV DOI: 10.25165/j.ijabe.20211403.4036 Citation: Liu X, Zhang W, Fu H B, Fu X M, Qi L Q. Distribution regularity of downwash airflow under rotors of agricultural UAV for plant protection. Int J Agric & Biol Eng, 2021; 14(3): 46–57.